2018
DOI: 10.3389/fpsyg.2018.02402
|View full text |Cite
|
Sign up to set email alerts
|

Application of Transtheoretical Model on Behavioral Changes, and Amount of Physical Activity Among University’s Students

Abstract: This study’s purpose was to examine the structural relationship of the transtheoretical model (TTM) and the amount of physical activity (PA) among undergraduate students in health and medicine at Universiti Sains Malaysia. A cross-sectional study was carried out among students who took part in the co-curricular program. Co-curricular program includes activities that take place outside of the regular lectures or tutorials in the University. Students recruited through purposive sampling were informed that their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
45
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 29 publications
8
45
0
2
Order By: Relevance
“…This reflects the gender enrolment ratio of Malaysia's public universities for the past two decades, in which females comprise almost two-thirds of the student population [47,48]. Other previous studies in our university also observed a high proportion of female respondents, ranging from 63 to 81% [49][50][51][52]. To obtain an equal ratio of male and female respondents, future studies should utilize stratified sampling method rather than convenience sampling method.…”
Section: Discussionsupporting
confidence: 56%
“…This reflects the gender enrolment ratio of Malaysia's public universities for the past two decades, in which females comprise almost two-thirds of the student population [47,48]. Other previous studies in our university also observed a high proportion of female respondents, ranging from 63 to 81% [49][50][51][52]. To obtain an equal ratio of male and female respondents, future studies should utilize stratified sampling method rather than convenience sampling method.…”
Section: Discussionsupporting
confidence: 56%
“…They were expected to better endure initiating and maintaining PA than the individuals with lower SEs. One study conducted among university students in Malaysia indicated that SE was associated with an individual’s behavioural changes related to exercise (20). Although there are many validated instruments available to measure SE, no properly validated instruments are available for measuring SE among different Malaysian populations.…”
Section: Introductionmentioning
confidence: 99%
“…To encourage individuals to engage in PA, the transtheoretical model (TTM) was introduced and used widely to reveal how an individual's behavioural change can be viewed as a process involving progression through a series of stages (pre-contemplation stage, contemplation stage, preparation stage, action stage and maintenance stage) [6]. The TTM consists of stages of readiness for change, processes of change, advantages and disadvantages of changing and self-efficacy that could help individuals switch to new behaviour through a series of changes [7]. Upon adopting a new behaviour, it is most important that a person has the right attitude and positive thoughts regarding the benefits of exercise.…”
Section: Introductionmentioning
confidence: 99%